(untitled) (International Journal of Studies in Nursing, 2019)
Background: Schwarz (1992) held that all people have personal values systems which guide them. However, the degree to which nursing staff can implement personal values in the workplace can vary depending on environment and institutional policy. This study examined the personal values of nursing staff and the gap between values and their implementation at work. Method: This was a quantitative descriptive study, using demographic information and a structured questionnaire, Schwartz’s Shorter Value Survey (SSVS), for examining the degree of implementation of personal values in clinical practice. Results: 425 respondents from different faiths assigned higher importance to certain values than to others, with demographic factors influencing decisions. Conclusion and Implications: Knowledge of the dominant personal values held by nursing staff may contribute to the organization’s ability to cultivate and maintain the human resources within it. Institutions should be aware of possible gaps between the importance of values and the degree of their implementation.